Information delivery: Communication in thriving for information / Siti Aishah Yahya - Yahya, Siti Aishah (2015)
It's begun at the late 19th century where people started to aware of information technology and information explosion. Information is a basis of the development and human civilization, as prove without information people cannot do comparisons and acknowledge the past a starting point for information delivery nowadays. Information delivery aimed to access and retrieve information in organized and authoritative ways. Information delivery can be referred as a process of sending, distributing and gaining information via network of technological approach to ease human communication. Nowadays, these approach was been practiced in many areas like business, agriculture, medical, academic institution and so on. Briefly, the usage was enlarger from day to day in facilitating people. Information delivery also exists from the development of communication as a subdivision in communication channels. Communication occurs when people using information delivery techniques as a channel to interpret data and delivery the information.